35‐4: Color holographic display using quantum‐dot doped liquid crystal. Issue 1 (29th May 2019) - Wang, Yunfeng; Li, Yan; Zhou, Pengcheng; Liu, Shuxin; Xu, Xinglei; Li, Xiang; Li, Sida; Chen, Quanming; Liu, Yueda; Ren, Xiuying; Su, Yikai
Abstract : We propose the use of a nematic liquid crystal (LC) doped with quantum dots (QDs) to realize a color 3D holographic display. The material has super large optical nonlinearity and could achieve a fast response time ~ 8.46ms. The constructed 3D display shows images at different depths and vivid RGB images at a video refresh rate.